The effect of project-based learning on students' reading skills viewed from grammatical competence and vocabulary at junior high school: a quasi-experimental study at SMPN 1 Kopang - Milhana, Anggi; Haerazi; Hidayatullah, Heri (Journal of English Language Proficiency, 2025)
This research aimed to determine the effect of Project-Based Learning (PBL) on students’ reading skills when viewed from grammatical competence and vocabulary mastery, as well as to examine the interaction between PBL and these two aspects. A quasi-experimental research design was employed in this study. The subjects were second-grade students of a junior high school English class. The sample consisted of 33 active students from Class B. Data were collected through classroom teaching activities and analyzed using tests of normality and homogeneity, an independent samples t-test, and a two-way ANOVA. The results revealed a significant effect of Project-Based Learning compared to the traditional method on students’ reading skills. The findings also showed an interaction between the learning method and students’ reading skills. However, no significant interaction was found between grammatical competence and vocabulary mastery in relation to Project-Based Learning. These results indicate that Project-Based Learning is effective in improving students’ reading skills, although its effectiveness is not influenced by students’ levels of grammatical competence and vocabulary mastery.